(untitled) (Bangladesh Journal of Agricultural Research, 2023)
A line × tester analysis comprising forty eight test-crosses generated by crossing 24 S3 inbred lines derived from commercial maize hybrid 981 with two testers. Heterosis study of these crosses against two standard checks was evaluated at Bangladesh Agricultural Research Institute, Gazipur during rabi 2015-16. The objectives of the study were to estimate general and specific combining ability effects of the inbred lines and to assess the test cross performance and estimate the amount of standard-heterosis of the hybrids for grain yield and yield related characters. Highly significant genotypic differences were observed indicated wide range of variability present among them. Five lines viz. Line 11, Line 14, Line 17, Line 24 and Line 30 were good general combiner for grain yield and possessed high means. Nine crosses showed (Line 18 × BIL22, Line 23 × BIL22, Line 27 × BIL22, Line 7 × BIL28, Line11 × BIL28, Line14 × BIL28, Line 24 × BIL28, Line 25 × BIL28 and Line 30 × BIL28) significant and positive specific combining ability effect for grain yield. The information on the nature of gene action with respective variety and characters might be used depending on the breeding objectives. These crosses, Line 24× BIL28 (11.40 t/ha), Line 18 × BIL22 (11.30 t/ha) and Line 25 × BIL28 (11.20 t/ha) showed higher yield, could be utilized in maize breeding activities. Estimation of heterosis was carried out using two commercial hybrids BARI Hybrid Maize-9 (BHM-9) and NK-40. The percent heterosis for grain yield varied from -23.39 to 4.6% against BHM-9. Among the 48 crosses, 13 crosses exhibited significant positive heterosis for grain yield. Bangladesh J. Agril. Res. 46(4): 469-489, December 2021